Hole‐Conductor‐Free Fully Printable Mesoscopic Solar Cell with Mixed‐Anion Perovskite CH3NH3PbI(3−x)(BF4)x. Issue 5 (17th December 2015) - Chen, Jiangzhao; Rong, Yaoguang; Mei, Anyi; Xiong, Yuli; Liu, Tongfa; Sheng, Yusong; Jiang, Pei; Hong, Li; Guan, Yanjun; Zhu, Xiaotong; Hou, Xiaomeng; Duan, Miao; et al.
Abstract : Mixed‐anion perovskite CH3 NH3 PbI(3 − x ) (BF4 ) x has been developed and optimized to enable a highly efficient hole‐conductor‐free fully printable mesoscopic solar cell. The employment of BF4 − in hybrid organic–inorganic halide perovskite significantly improves its optical and electric properties, such as light harvesting ability, carrier concentration, and conductivity, leading to an enhanced power conversion efficiency of 13.24%.